Use of Fig Seed Meal as a New Alternative Feed Source in Quails: Effect on Growth Performance, Carcass Characteristics, Antioxidant Capacity and Serum Biochemistry - Irmak, Mehmet; Denli, Muzaffer; Sahin, Nurhan; Tufan, Tuncay; Irak, Kivanc; Kayri, Veysi; Ipcak, Hasan Huseyin (Wiley, 2025)
This study aims to evaluate the potential of fig seed meal (FSM), which contains approximately 20% crude protein (CP) and provides 2106 kcal/kg of metabolizable energy (ME), as an alternative protein source in the diets of broiler Japanese quails (Coturnix coturnix japonica). One hundred sixty 1-day-old mixed-sex quails were divided into four groups, each with four replicates, and fed diets containing 0% (control), 2.5%, 5.0% and 10.0% FSM for 35 days. Weekly growth performance parameters were recorded, and carcass characteristics and blood biochemical parameters were analysed at the end of the trial. Including up to 10% FSM did not affect feed intake (FI) (p > 0.05), but linear, quadratic and cubic effects were observed in body weight gain (BWG). Adding up to 5% FSM resulted in growth performance similar to the control group, whereas the 10% FSM diet significantly reduced BWG. FSM levels influenced the feed conversion ratio (FCR) linearly, quadratically and cubically, with a decline observed at levels above 5%. In female quails, 5% FSM increased breast and thigh weights, whereas in males, it reduced carcass yield and intestinal weight. There were no statistically significant differences in other carcass traits among the groups. Serum biochemical parameters and oxidant/antioxidant balance were not adversely affected by FSM inclusion up to 5%. In conclusion, using FSM up to 5% did not negatively impact growth performance, but higher inclusion levels reduced performance.
Keywords: carcass characteristics; fig seed meal; growth performance; quails; serum biochemistry